Systematic review and classification of: Adolescent Coping with Depression Course - Skotheim, Siv; Wergeland, Gro Janne; Kvello, Øyvind (Ungsinn. Journal of Effective Interventions for Children and Adolescents, 2024)
Background: This article is a systematic review of the effects of the Adolescent Coping with Depression Course (ACDC, in Norwegian called DU-Mestringskurs for ungdom). It is a revision of previous reviews (Wergeland, Skotheim & Kvello, 2016; Kvello, 2013), and updated according to the new classification criteria in Ungsinn (Martinussen et al., 2019). ACDC is a 10-session manual-based intervention for adolescents, 14-20 years old, with elevated levels of depressive symptoms or with mild to moderate depression. The main purpose of the ACDC is reduce depressive symptoms, as well as relapse prevention. The purpose of this review is to examine whether the intervention is effective when used in ordinary practice in Norway.Method: The following databases were searched to find relevant articles: Embase, Medline and Psycinfo, NORART Cochrane, Oria, NORA and SweMed, reports from helsebiblioteket, NICE and Bluprint, as well as information from the developer of the intervention.Results: The intervention is well described through a detailed manual and several other documents. The intervention is based on cognitive behavioral therapy. The literature search resulted in two Nordic studies: one pre-post study and one randomized controlled study (RCT)) with assessment at twelve months follow-up. Both studies showed a reduction in the adolescents’ level of depressive symptoms during the intervention with a small to moderate effects size. However, the RCT study showed no difference between the intervention-and control group after six and twelve months. The intervention owner has a system to ensure implementation quality. In the RCT study fidelity was assessed using a fidelity model developed by the National Institutes of Health’s Behavior Change ConsortiumConclusion: The intervention is well described in several documents including a detailed manual. The aims of the intervention and target groups are well defined. The two studies indicate that the ACDC intervention has a positive effect on the level of depressive symptoms in adolescents, however there are still some methodological concerns related to both statistical power and internal validity in the RCT study. The evidence level approaches level 4, but as there are still some methodological limitations the Adolescent Coping with Depression Course (ACDC) is classified at level 3: Interventions with some documentation of effect.
Keywords: Systematic review; Adolescent Coping with Depression Course; Depression